2008
DOI: 10.1021/ja801983d
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous Identification of Möbius Aromaticity formeso-Aryl-Substituted [28]Hexaphyrins(1.1.1.1.1.1)

Abstract: meso-Aryl-substituted [28]hexaphyrins(1.1.1.1.1.1) have been examined by (1)H, (13)C, and (19)F NMR spectroscopies, UV-vis absorption spectroscopy, magnetic circular dichroism spectroscopy, and single-crystal X-ray diffraction analysis. All of these data consistently indicate that [28]hexaphyrins(1.1.1.1.1.1) in solution at 25 degrees C exist largely as an equilibrium among several rapidly interconverting twisted Möbius conformations with distinct aromaticities, with a small contribution from a planar rectangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
237
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(259 citation statements)
references
References 50 publications
13
237
2
7
Order By: Relevance
“…We expect that higher NLOP values and larger differences between NLOP of Möbius and Hückel conformations can be obtained in expanded porphyrins with larger differences of aromaticity (and HOMO-LUMO gaps) between both topologies, and where the Möbius structure is most stable than the Hückel one. Additional work on the NLOP evaluation of meso-aryl-substituted [28]hexaphyrins(1.1.1.1.1.1), 8 and a deep analysis between the aromaticity, global hardness, and NLOP of the expanded porphyrins using the maximum hardness and minimum polarizability principles 44 are in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expect that higher NLOP values and larger differences between NLOP of Möbius and Hückel conformations can be obtained in expanded porphyrins with larger differences of aromaticity (and HOMO-LUMO gaps) between both topologies, and where the Möbius structure is most stable than the Hückel one. Additional work on the NLOP evaluation of meso-aryl-substituted [28]hexaphyrins(1.1.1.1.1.1), 8 and a deep analysis between the aromaticity, global hardness, and NLOP of the expanded porphyrins using the maximum hardness and minimum polarizability principles 44 are in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The conformational flexibility, the number and the nature of substituents on the pyrrolic and meso positions, and the metallation of the porphyrins allow them to achieve different topologies with distinct aromaticities, magnetic, and electric properties. 4 In the last five years several Hückel and Möbius topological systems have been prepared through replacement of the solvent and protonation, [5][6][7] temperature control, 8,9 metal coordination, 10 and functional group modifications. 11 As one can see, the synthesis of aromatic systems with Möbius topology has just started and there are still a lot of aspects and applications to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…[24] In subsequent reports it was shown that the ability to stabilize Möbius structures is a more general feature of porphyrinoids, and that the topology adopted by the macrocycle can be controlled to some extent. [25,26,103,110,[120][121][122][123][132][133][134] While the occurrences of Möbius aromaticity are still relatively rare, they are more frequent than could be expected. In fact, as we will discuss in more depth later, certain instances of Möbius topology (not always coinciding with well-defined aromatic character) were published in earlier porphyrinoid literature and remained unrecognized until recently.…”
Section: Möbius Aromaticitymentioning
confidence: 98%
“…[24] Später wurde gezeigt, dass die Fähigkeit zur Stabilisierung von Möbius-Strukturen eine allgemeine Eigenschaft der Porphyrinoide ist und die Topologie des Makrocyclus zu einem gewissen Maß kontrolliert werden kann. [25,26,103,110,[120][121][122][123][132][133][134] Möbius-Aromatizität kommt zwar relativ selten vor, aber dennoch weit häufiger, als man zunächst erwarten könnte. Weiter unten werden wir auf bestimmte Beispiele zur Möbius-Topologie, die eigentlich schon lange Bestandteil der Porphyrinoid-Literatur sind, aber bis vor kurzem nicht als solche erkannt worden waren, näher eingehen.…”
Section: Möbius-aromatizitätunclassified
“…[236] Diese Merkwürdigkeit konnte zunächst nicht geklärt werden, bis neun Jahre später die Struktur von 41c-H 4 in Lösung durch Tieftemperatur-NMR-Spektroskopie und andere physikalische Methoden erneut analysiert wurde. [121,123] Nach diesen Studien wechselt 41c-H 4 sehr rasch zwischen vier gleichwertigen Möbius-Konformationen (T1), hat aber eine Zwischenstufe der Konformation T0 AD mit konstanter Stellung der invertierten Ringe (Schema 17). Aus diesem Grund weist das dynamisch gemittelte Raumtemperaturspektrum von 41c-H 4 die gleiche Symmetrie auf wie das von 40c-H 2 .…”
Section: Rubyrineunclassified